Development of a performance threshold approach for identifying the management options for stabilisation/solidification of lead polluted soils - Falciglia, Pietro Paolo; Al-Tabbaa, Abir; Vagliasindi, Federico G. A. (Journal of Environmental Engineering and Landscape Management, 2014)
Two soils spiked with lead at different rates were stabilised/solidified using Portland cement and fy ash at different soil:binder ratios, and tested for their setting time, unconfined compressive strength, leachability and durability. A performance threshold approach was used in order to identify optimal management options for the products of the S/S treatment. Results show that soil texture, percentage of binders and lead concentration play an important part in the treatment, significantly influencing the performance of the resulting products in terms of curing, compressive strength and durability. Pb soil concentrations higher than 15000 mg kg-1 were found to heavily reduce the applicability of the treatment requiring the maximum amount of binder in order to satisfy the performance criteria. Te performance of sandy soils was shown to be limited by setting time and UCS features due to the retardation of the hydration reactions and also by its leaching behaviour, whereas for silt-clayey soils the critical parameter is the mechanical resistance. First published online: 19 Mar 2014